Pedagogical Competence of Elementary School Teachers in Multiliteracy Learning within Independent Curriculum - Hanum Hanifa Sukma; Rashika Ardafa Sahila; Yeyen Febrilia (Universitas Sebelas Maret, 2024)
This research aims to determine the pedagogical competence of elementary school teachers in implementing multiliteracy learning in the Merdeka Curriculum, especially the practical part in the classroom, and to find out the supporting and inhibiting factors experienced by teachers in implementing multiliteracy learning in the Merdeka Curriculum in teaching and learning practices in the school. The research was carried out. This research uses a descriptive qualitative approach. Data collection uses observation, interviews, and documentation with analysis techniques with validity tests according to Miles Huberman and NVivo 12 Plus software. The results of this research show that teachers at SD Negeri 2 Pejawaran have implemented pedagogical competence well, characterized by a safe and comfortable learning environment for students in multiliteracy learning, student-centered learning in multiliteracy learning, Assessment, feedback and reporting that is centered on multiliteracy learning students, Using diverse sources of learning information, Critical evaluation of sources of information, Production, presentation, and variety of information through various texts, Supporting the use of multiliteracy to promote goodness. The supporting factors are fellow teachers, reading corner, students, library, Merdeka Mengajar application, and Mading. Apart from that, the inhibiting factor is the availability of books in the school library.